ONCOPLASTIC MAMMAPLASTY WITH DISGUISED GEOMETRIC COMPENSATION - Paulinelli, Régis Resende; Ribeiro, Luiz Fernando Jubé; Santos, Thauana Dias; Caires, Elisana Maria Santos; Pontes, Marilha Gabriella Martins; Faria, Bruna Morais (Mastology, 2021)
Objective: To evaluate the results and follow-up of retrospective cohort of patients submitted to a new technique of oncoplastic mammaplasty, referred to as disguised geometric compensation mammaplasty (DGCM), which is suitable for tumors involving the glandular tissue in the lateral or medial pillars of the mammaplasty. Materials and Methods: A total of 25 patients with breast tumor involving the pillars of the mammaplasty were included, of whom 20 (80.00%) had invasive ductal carcinoma, 3 (12.00%) had phyllodes tumor, 1 (4.00%) had invasive lobular carcinoma, and 1 (4.00%) had in situ ductal carcinoma. Preoperative markings followed the “Wise-pattern” technique. The resection of the tumor in the pillar of the mammaplasty, preserving the overlying skin, was geometrically compensated with a correspondent area coming from the lower poles, which folds over itself and maintains the skin vascularity in the pillar. One patient was converted to classic geometric compensation due to a positive skin margin in the frozen section. Other patient combined a classic geometric compensation for the inner quadrants and DGCM for the outer quadrants in the same breast. One patient decided to submit to a bilateral mastectomy after adjuvant chemotherapy because of a BRCA2 mutation. Immediate fat grafting was done in one case. Approval from the ethics committee: n. 2.322.212. Results: Mean age was 46.96±9.53 years. Mean clinical tumor size was 47.21±22.16 mm before chemotherapy and 36.67±22.5 mm after chemotherapy. There were 11 (44.00%) locally advanced and 1 (4.00%) multicentric tumor. Nine (36.00%) patients were submitted to neoadjuvant chemotherapy. Adjuvant chemotherapy, endocrine therapy, and radiotherapy were indicated according to the necessity. Ptosis was corrected in all cases. The aesthetic results were rated as excellent or good in 21 cases (95.45%) by the Harvard scale and the BCCT.core. Three patients have not returned for the aesthetic evaluation after surgery. The BREAST-Q scores for the satisfaction with the breasts and satisfaction with outcomes were 81.50 (±15.00) and 90.44 (±11.70), respectively. Intraoperative frozen sections were done in 12 (48%) cases. There were two (8.00%) positive margins. One focus of DCIS in the skin margin was treated with radiotherapy, and the other positive margin was treated with re-excision. The complications were: three (12.00%) small wound dehiscences, two (8.00%) small skin necrosis, and two (8.00%) local hyperemia treated with antibiotics, two (8.00%) enlarged scars, and one (4.00%) small hematoma. There were not reoperations to treat complications. There was 1 (4.00%) local recurrence in the breast and axilla after 11 months, treated with radical mastectomy, and 1 (4.00%) metastasis to the brain after 3 months. No deaths were observed within a mean follow-up time of 16.28±11.39 months. Conclusion: The technique allowed breast conservation in situations requiring large resection in the pillars of the mammaplasty, with a high rate of free margins, correction of ptosis, satisfactory symmetry, and few complications.